Chapter 10 The Ethics of Genetic Enhancement Key Concepts and Future Prospects - Anomaly, Jonny (Taylor & Francis, 2024)
The desire to transform ourselves into something better than we are now is as old as humanity. But the ability to use biomedical technologies to enhance our capacities is new. In this chapter, we will distinguish different forms of enhancement - for example, environmental, biochemical, and genetic interventions aimed at improving existing capacities. But we will focus on genetic enhancement. We will ask whether there is any interesting difference between treating diseases and enhancing existing capacities. We will discuss reasons people may have to enhance their children, and moral concerns that opponents of enhancement have expressed, such as discrimination against disabled or unenhanced people in a world in which enhancement is common. Finally, we will address how to think about human enhancement from a social standpoint, where each person's choices to enhance themselves or their children has network effects on the human population as a whole.